2013
DOI: 10.1002/ece3.729
|View full text |Cite
|
Sign up to set email alerts
|

A multievent approach to estimating pair fidelity and heterogeneity in state transitions

Abstract: Fidelity rates of pair-bonded individuals are of considerable interest to behavioral and population biologists as they can influence population structure, mating rates, population productivity, and gene flow. Estimates of fidelity rates calculated from direct observations of pairs in consecutive breeding seasons may be biased because (i) individuals that are not seen are assumed to be dead, (ii) variation in the detectability of individuals is ignored, and (iii) pair status must be known with certainty. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 59 publications
3
48
0
Order By: Relevance
“…It is often recommended to parameterize the observation process (here: detection and assignment), before the biological one (e.g. Culina, Lachish, Pradel, Choquet, & Sheldon, ). Starting with a constant‐only model, we sequentially parameterized the: (1) assignment of infection states, (2) detection, (3) survival, (4) infection, (5) social transitions and (6) breeding transitions, testing for effects of social, demographic and infection states on those processes.…”
Section: Methodsmentioning
confidence: 99%
“…It is often recommended to parameterize the observation process (here: detection and assignment), before the biological one (e.g. Culina, Lachish, Pradel, Choquet, & Sheldon, ). Starting with a constant‐only model, we sequentially parameterized the: (1) assignment of infection states, (2) detection, (3) survival, (4) infection, (5) social transitions and (6) breeding transitions, testing for effects of social, demographic and infection states on those processes.…”
Section: Methodsmentioning
confidence: 99%
“…We believe that the survival costs of changing partners may be profound within and between seasons, but all the work done so far in the context of survival has been on betweenseason mate fidelity (Nicolai et al 2012, Culina et al 2013, 2015b. To the best of our knowledge, this analysis is the first to additionally explore the problem of within-season faithfulness in terms of apparent survival costs related to the costs of reproduction.…”
Section: Aimsmentioning
confidence: 99%
“…A series of conditional probabilities allows each event to be related to one or more states. Culina et al (2013) defines seven possible exclusive events which can be observed in the studied population as: 1) event 0 = the focal individual is not captured in the current breeding season (i.e. at t), its partner from the previous season (t -1) is either not captured at t -1 or t, or is captured breeding at t at an active nest with an unknown partner; 2) event 1 = the focal individual is captured at t and is breeding with its partner from t -1; 3) event 2 = the focal individual is captured at t but is breeding with a different partner to that from t -1; 4) event 3 = the focal individual is captured at t but it is not known whether its current partner, which is captured, is the same as the one from t -1; 5) event 4 = the focal individual is captured at t, its current partner is not captured, but its partner from t -1 is captured at t at a different nest (and hence is not breeding with the focal individual at t); 6) event 5 = the focal individual is captured at t, its current partner is not captured, and its partner from t -1 is either not captured at t or was not known at t -1; 7) event 6 = the focal individual is not captured at t (and hence its current partner is unknown), but its partner from t -1 is captured breeding with another individual at t.…”
Section: Model Designmentioning
confidence: 99%
“…Results of a few studies suggest that divorce (and other forms of partner change) might also negatively affect survival (Nicolai et al, 2012;Culina et al, 2013). Results of a few studies suggest that divorce (and other forms of partner change) might also negatively affect survival (Nicolai et al, 2012;Culina et al, 2013).…”
Section: (2) Challenges In Estimating Post-divorce Successmentioning
confidence: 99%